Religiosity and Its Impact on Energy Consumption in Indonesian Muslim Households - Arkania Choirin Tameema; Djoni Hartono; Misdawita (Department of Development Economics, Universitas Sriwijaya, 2026)
This study examines the underexplored relationship between religiosity and household energy consumption, applying religious behavior theory to energy economics in Indonesia—the world’s largest Muslim-majority nation. While traditional models focus on socioeconomic determinants, this paper investigates how Islamic values influence electricity consumption, explicitly addressing the inherent endogeneity of self-reported religiosity. Utilizing data from the Indonesian Family Life Survey (IFLS-5) comprising 21,023 Muslim households, we employ a two-stage least squares (2SLS) instrumental variable approach, proxying religiosity through ritual frequency and religious practices to overcome omitted variable and self-selection biases. The empirical results reveal a robust, statistically significant negative relationship between higher levels of religiosity and household electricity expenditure. This finding aligns with the theoretical framework that religious tenets foster moderation, self-control, and environmental stewardship. The results remain resilient across extensive sensitivity analyses and alternative model specifications. Culturally, these findings imply that faith-based institutions and religious leaders are powerful, cost-effective conduits for behavioral energy conservation. Integrating moral paradigms into national climate strategies offers a potent, localized mechanism to complement standard efficiency policies and accelerate carbon emission reductions in emerging Muslim-majority economies.